Quasiperiodic Slow-propagating Extreme-ultraviolet “Wave” Trains after the Filament Eruption - Yining Zhang; Ting Li; Weilin Teng; Xinping Zhou; Yijun Hou; Zheng Sun; Xuchun Duan; Yilin Guo; Guiping Zhou (The Astrophysical Journal Letters)
The eruption of the filament/flux rope generates the coronal perturbations, which further form extreme-ultraviolet (EUV) waves. There are two types of EUV waves, namely, fast-mode magnetosonic waves and slow waves. In this Letter, we first report an event showing the quasiperiodic slow-propagating (QSP) EUV “wave” trains during an M6.4-class flare (SOL2023-02-25T18:40), using multiple observations from Solar Dynamics Observatory (SDO)/Atmospheric Imaging Assembly (AIA), Chinese Hα Solar Explorer (CHASE)/Hα Imaging Spectrograph (HIS), Advanced Space-based Solar Observatory (ASO-S)/Full-disk vector MagnetoGraph (FMG), SUTRI, and Large Angle and Spectrometric Coronagraph (LASCO)/C2. The QSP “wave” trains occurred as the filament showed a rapid rise. The QSP “wave” trains have the projected speeds of 50–130 km s ^−1 on the plane of the sky, which is slower than the fast-mode magnetosonic speed in the solar corona. And the calculated period of the QSP wave trains is 117.9 s, which is in good agreement with the associated flare quasiperiodic pulsation (140.3 s). The QSP wave trains could be observed during the entire impulsive phase of the flare and lasted about 30 minutes in the field of view (FOV) of SDO/AIA. About 30 minutes later, they appeared in the FOV of LASCO/C2 and propagated to the northwest. We suggest that the QSP wave trains are probably apparent waves that are caused by the successive stretching of the inclined field lines overlying the eruptive filament. The periodic pattern of the QSP wave trains may be related to the intermittent energy release during the flare.